PENGARUH PERMAINAN HURUF PUNGGUNG BERANTAI TERHADAP KEMAMPUAN ANAK MENGENAL HURUF PADA USIA 5-6 TAHUN DITAMAN KANAK-KANAK MASMUR KECAMATAN SIAK HULU KABUPATEN KAMPAR - Mery Melinda; Wilson '; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The research is to know backs chain letters game to know your child’s ability letters intelligence in masmur kindergarten district siak hulu kampar regency. The sample of population in this research is 5-6 years old to amount to 15 person’s. to collect the data is observation technics. To analysis data used in this research is test-t. the result of research is obtained from the sample result of hypothesis test correlation, with the before and after values of r = 0,862 and the value of significance is 0,000. Because, p<0,05 (0,862<0,05) then Ho rejected. The means of research is backs chain letters game to know your child’s ability letters on age 5-6 years children’s intelligence. To receive or reject hypothesis based on SPSS data windows for version 17 then can be seen from a comparison t value and t table is calculation of the test-t, seen that result t value -13,412 from the parties of absolutely price, so the minus (-) price cannot be used(Sugiyono, 2010). Then value (-13,412). DK= 40 and the fault stage 5%= 2,021). The mean Ho= were rejected and Ha= accepted. From the research have conslussion that’s the backs chain letters game is be effective to know your child’s ability letters on age 5-6 years olds children’s intelligence.Key words : child’s ability letters, backs chain letters game